Efficacy of anthelmintics against gastrointestinal nematodes of pigs in Tripura, India - DE, ANKAN; DAS, SUBHAM; PANDIT, SOUMITRA; JAS, RUMA; BAIDYA, SURAJIT; MANDA, SUBHAS C; DEBBARMA, APURBA; BATABYAL, SUBHASIS (The Indian Journal of Animal Sciences, 2025)
Pig husbandry plays a pivotal role in providing subsidiary source of income to the economically weaker section of people in rural areas of Tripura, a north-eastern state of India. However, gastrointestinal (GI) nematode infection is one of the prime constraints in profitable pig husbandry in the state. Though, anthelmintic drugs are commonly used in treatment of such cases, reduced effectiveness has been observed for some of the commonly used drugs. Therefore, the present study was conducted to assess the efficacy of four common anthelmintics viz., albendazole, fenbendazole, ivermectin and piperazine on GI nematodes of pigs in Tripura using faecal egg count reduction test (FECRT). Fecal samples were collected from a total of 50 randomly selected pigs at pre-treatment and 10-days post- treatment. The highest FECR percent was shown by ivermectin (97.32%) and the lowest by albendazole (88.39%). The results indicate the effectiveness of ivermentin and at the same time, development of resistance against albendazole in GI nematodes of pigs in the study area. This is the first ever report on efficacy of the anthelmintic drugs on GI nematodes of pigs in Tripura. The study provides baseline information which can be further confirmed by using molecular techniques.